Identifying New COVID-19 Receptor Neuropilin-1 in Severe Alzheimer’s Disease Patients Group Brain Using Genome-Wide Association Study Approach - Lim, Key-Hwan; Yang, Sumin; Kim, Sung-Hyun; Joo, Jae-Yeol (Frontiers in Genetics, 2021)
Recent preclinical studies have shown that Neuropilin-1 (NRP1), which is a transmembrane protein with roles in neuronal development, axonal outgrowth, and angiogenesis, also plays a role in the infectivity of SARS-CoV-2. Thus, we hypothesized that NRP1 may be upregulated in AD patients and that a correlation between AD and SARS-CoV-2 NRP1-mediated infectivity may exist as ACE2. We used an AD mouse model that mimics AD and performed high throughput total RNA-seq with brain tissue and whole blood. For quantification of NPR1 in AD, brain tissues and blood were subjected to western blotting and RT-qPCR analysis. In silico analysis for NRP1 expression in AD patients has been performed on the human hippocampus data sets. Many cases of severe symptom of COVID-19 are concentrated in elderly group who have complications such as diabetes, degenerative disease, and brain disorders. Total RNA-seq analysis showed that Nrp1 gene was commonly overexpressed in AD model. Similar to ACE2, NRP1 protein also strongly expressed in the AD brain tissues. Interestingly, in silico analysis revealed that the level of expression for NRP1 was distinct at age and AD progression. Given that the NRP1 is highly expressed in AD, it will be important to understand and predict that NRP1 may a risk factor for SARS-CoV-2 infection in AD patients. This will support to development of potential therapeutic drug to reduce SARS-CoV-2 transmission.